The effect of diamagnetic flows on turbulent driven ion toroidal rotation - Lee, J; Barnes, M; Parra, F; Belli, E; Candy, J (American Institute of Physics Inc., 2014)
Turbulent momentum redistribution determines the radial profile of rotation in a tokamak. The momentum transport driven by diamagnetic flow effects is an important piece of the radial momentum transport for sub-sonic rotation, which is often observed in experiments. In a non-rotating state, the diamagnetic flow and the E × B flow must cancel. The diamagnetic flow and the E × B flow have different effects on the turbulent momentum flux, and this difference in behavior induces intrinsic rotation. The momentum flux is evaluated using gyrokinetic equations that are corrected to higher order in the ratio of the poloidal Larmor radius to the minor radius, which requires evaluation of the diamagnetic corrections to Maxwellian equilibria. To study the momentum transport due to diamagnetic flow effects, three experimental observations of ion rotation are examined. First, a strong pressure gradient at the plasma edge is shown to result in a significant inward momentum transport due to the diamagnetic effect, which may explain the observed peaking of rotation in a high confinement mode. Second, the direction of momentum transport is shown to change as collisionality increases, which is qualitatively consistent with the observed reversal of intrinsic rotation by varying plasma density and current. Last, the dependence of the intrinsic momentum flux on the magnetic shear is found, and it may explain the observed rotation changes in the presence of lower hybrid current drive. © 2014 AIP Publishing LLC.